2021
DOI: 10.1155/2021/8844356
|View full text |Cite
|
Sign up to set email alerts
|

Foot Posture Index Reference Values among Young Adults in Saudi Arabia and Their Association with Anthropometric Determinants, Balance, Functional Mobility, and Hypermobility

Abstract: Background. The foot posture index (FPI) is a valid, reliable, and multidimensional method for determining foot posture in a wide range of clinical settings. To date, no normative data of healthy young adults in Saudi Arabia have been available for comparison and reference. Hence, this study is aimed at establishing the FPI reference values, gender, and side differences of FPI and their association with anthropometric determinants, balance, functional mobility, and hypermobility. Methods. FPI was assessed in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The majority of GJH participants had altered their left and right feet. Other scientific sources state that there is a relationship between ligament laxity and foot pronation [ 15 , 57 ]. In contrast, there is a study suggesting that joint hypermobility does not affect the medial longitudinal arches of the feet in adults [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of GJH participants had altered their left and right feet. Other scientific sources state that there is a relationship between ligament laxity and foot pronation [ 15 , 57 ]. In contrast, there is a study suggesting that joint hypermobility does not affect the medial longitudinal arches of the feet in adults [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the most common foot posture in both genders ranged from neutral to slight pronation in the Saudi Arabian population [ 9 ]. They also reported the existence of a significant correlation between balance and FPI in the supinated and hyper-supinated foot groups and between functional mobility and FPI of the pronated foot.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, there are several methods for analyzing foot posture in standing position, including X-raying the foot, taking footprints, foot posture index (FPI), arch height index, and navicular drop test. The FPI requires no specialized equipment and has been found to be a reliable and user-friendly test for medical fraternity to evaluate normative scores across varied populations [ 9 ]. Balance is the maintenance of the body’s center of gravity within its support base.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some researchers provided anthropometric data in Saudis regarding hand anthropometrics of engineering students that may aid in designing various devices and machines [40]. Another study aimed to establish foot posture index reference values in healthy Saudi adults that may be used in a range of clinical settings [41]. Furthermore, plastic and reconstructive surgeries in Saudi women have increased [42].…”
Section: Other Anthropometrics Assessed In Healthy Saudismentioning
confidence: 99%